Editorial da Revista Contabilidade & Inovação: Ano de 2023 - Lima Soares, Juliano; Elisa Sarmento Costa, Maria (Revista Contabilidade & Inovação, 2023)
Editorial da Revista Contabilidade & Inovação: Ano de 2023